2003
DOI: 10.1016/s1063-4584(03)00167-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification, quantification and isolation of mesenchymal progenitor cells from osteoarthritic synovium by fluorescence automated cell sorting

Abstract: Our results show that SM from OA patients contains cells that express typical combinations of MPC surface markers and have the potency of osteogenic and chondrogenic differentiation. Their relative enrichment during in vitro cultivation and the possibility of cell sorting to get more homogenous populations offer interesting perspectives for possible future therapeutic applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
95
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(102 citation statements)
references
References 23 publications
5
95
0
2
Order By: Relevance
“…Recently, results on the phenotypic characterization of cells derived from human synovium were published. 3,39 Cell sorting by flow cytometry is frequently used to isolate specific cells from heterogeneous populations. [39][40][41] Researchers have tried to clarify stem cell-and progenitor cell-specific surface antigens, and then to isolate potential cells possessing these antigens.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, results on the phenotypic characterization of cells derived from human synovium were published. 3,39 Cell sorting by flow cytometry is frequently used to isolate specific cells from heterogeneous populations. [39][40][41] Researchers have tried to clarify stem cell-and progenitor cell-specific surface antigens, and then to isolate potential cells possessing these antigens.…”
Section: Discussionmentioning
confidence: 99%
“…3,39 Cell sorting by flow cytometry is frequently used to isolate specific cells from heterogeneous populations. [39][40][41] Researchers have tried to clarify stem cell-and progenitor cell-specific surface antigens, and then to isolate potential cells possessing these antigens. For adult MSCs, some authors suggested that Stro-1, CD105, CD90, CD44, and CD166 are specific antigens for BM or perichondrium-derived MSCs, and that CD9, CD90, and CD166 are chondrogenic markers for synovium-derived MSCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…General consensus has not yet been established regarding specific cell surface markers [4]. It is not possible to characterize these cells only by the use of one specific cell marker [41]. Different protocols are applied to compare MSCs from different sources, always respecting the minimal criteria proposed by the ISCT.…”
Section: Msc Sources Applicable For Musculoskeletal Regenerationmentioning
confidence: 99%
“…Another potential hurdle to overcome with the use of any cell type harvested from the same joint that possesses a damaged meniscus is the impact of the subsequent osteoarthritis on those cells' chondrogenic capabilities. However, it has recently been confirmed that SMSCs obtained from human patients with end-stage knee osteoarthritis express typical combinations of mesenchymal progenitor surface markers and retain the potential for chondrogenic differentiation [29]. Hoben's final ''ideal cell'' criteria regarding the ability to produce robust fibrocartilaginous matrix is simultaneously challenging and yet ill-defined [43].…”
Section: Synovial-based Cellsmentioning
confidence: 99%